How Online Fraud Victims are Targeted in China: A Crime Script Analysis of Baidu Tieba C2C Fraud - Lee, Claire Seungeun (Crime & delinquency, 2022)
E-commerce is the practice of purchasing, selling, transferring, and exchanging goods, services, or information through the Internet, a computer, and/or other devices. With the development of e-commerce markets, fraud is increasingly reported. This study uses a crime script analysis to examine how customer-to-customer (C2C) fraud occurs on China?s online platforms with a particular focus on the online marketplace Baidu Tieba and Tencent QQ, a tool that allows customers to make contact and negotiate deals and payment methods. The findings demonstrate that C2C fraud develops through pre-operation, operation, finalization, and exit stages, sharing commonalities with other online identity fraud processes. Implications for policy and interventions are also discussed in regard to e-commerce fraud in China and elsewhere.